Designing sustainable polymers: lactate esters for 3D printing and upcycling - Klee, Pia S.; Vázquez-Martel, Clara; Flórido Martins, Lilliana; Blasco, Eva (ACS applied polymer materials, 2024)
The search for sustainable polymer systems is key to tackling the current climate crisis. However, the use of biobased polymers does not suffice to achieve this goal. Additionally, chemical approaches enabling the recycling or upcycling of polymer materials need to be explored. Herein, we exploit lactate esters with different substituents as readily available biobased molecules for the synthesis of printable monomers. The synthesis of these lactate ester-based monomers follows green chemistry principles by establishing a solvent-free, one-pot approach, relying on a reusable catalyst, and achieving high conversions (84-100%) under mild conditions. Further, these monomers are utilized in 3D printable ink formulations for digital light processing (DLP) for the first time in combination with a recycled crosslinker. The resulting 3D printed structures display complex geometries with high resolution. A key attribute of the presented system is that the 3D printed polymer material can be upcycled via aminolysis affording a precursor of the crosslinker, which is in turn incorporated into further ink formulations, introducing a material circularity into the system. These results demonstrate a strategic combination of a biobased monomer and chemical upcycling with sustainable 3D printing techniques.
Online veröffentlicht: 25. Dezember 2023
Gesehen am 20.02.2024